Molecular Diagnostics of Coronavirus Infection in the Kyrgyz Republic - S. V. Khegay; A. K. Dzhaparova; E. M. Dushenalieva; B. Kalmyrzaev; K. T. Kasymbekova; T. E. Kuchuk; N. T. Usenbaev; A. T. Zhunushov (Проблемы особо опасных инфекций, 2020)
Abstract. Objective of the study was to develop an effective method of sample pooling for the detection of SARSCoV-2 coronavirus RNA using PCR and evaluate that approach with various test systems.Materials and methods. SARS-CoV-2 coronavirus RNA was detected in samples containing nasal swabs placed in a transport medium. 5 samples were combined into one pool to perform the analysis. The effectiveness of the “in single test tube” pooling method for performing mass studies for COVID-19 was evaluated using the Vector-PCRrv-2019-nCoV-RG-19 test systems,Russia; “ArtTest COVID-19”,Belarus; “BioSpeedy”,Turkey.Results and discussion. A total of 587 pools were studied, consisting of 2935 test samples, in which 56 samples containing SARS-CoV-2 RNA were detected and confirmed by PCR. When studying the method of pooling samples, its specificity and optimal sensitivity for detecting SARS-CoV-2 RNA using the Vector-PCRrv-2019-nCoV-RG, ArtTest COVID-19, and BioSpeedy test systems were shown. The results of applying the pooling method correlated with the data obtained without pooling samples. The average deviation of the cycle amounted to 2 Ct; the fluorescence curve of positive samples corresponded to the «S» form.